2006
DOI: 10.1016/j.neuron.2006.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Targeted In Vivo Mutations of the AMPA Receptor Subunit GluR2 and Its Interacting Protein PICK1 Eliminate Cerebellar Long-Term Depression

Abstract: Cerebellar long-term depression (LTD) is a major form of synaptic plasticity that is thought to be critical for certain types of motor learning. Phosphorylation of the AMPA receptor subunit GluR2 on serine-880 as well as interaction of GluR2 with PICK1 have been suggested to contribute to the endocytic removal of postsynaptic AMPA receptors during LTD. Here, we show that targeted mutation of PICK1, the GluR2 C-terminal PDZ ligand, or the GluR2 PKC phosphorylation site eliminates cerebellar LTD in mice. LTD can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
301
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(322 citation statements)
references
References 41 publications
20
301
1
Order By: Relevance
“…Knock-in mice expressing GluA1 or GluA2 subunits mutated to non-phosphorylatable or phosphomimetic residues have demonstrated that phosphorylation of GluA1 by CaMKII or PKA is necessary for full hippocampal LTP expression 134 , while dephosphorylation of the PKA site in GluA1 is required for LTD 46 . Furthermore, PKC phosphorylation of GluA2 is required for cerebellar LTD 135 . Beyond GluA1 and GluA2, transient expression of GluA4 in CA1 pyramidal neurons during early development underpins the switch in kinase signaling in LTP from PKA to CaMKII-dependent mechanisms 136 .…”
Section: Ampar Phosphorylationmentioning
confidence: 99%
“…Knock-in mice expressing GluA1 or GluA2 subunits mutated to non-phosphorylatable or phosphomimetic residues have demonstrated that phosphorylation of GluA1 by CaMKII or PKA is necessary for full hippocampal LTP expression 134 , while dephosphorylation of the PKA site in GluA1 is required for LTD 46 . Furthermore, PKC phosphorylation of GluA2 is required for cerebellar LTD 135 . Beyond GluA1 and GluA2, transient expression of GluA4 in CA1 pyramidal neurons during early development underpins the switch in kinase signaling in LTP from PKA to CaMKII-dependent mechanisms 136 .…”
Section: Ampar Phosphorylationmentioning
confidence: 99%
“…The other is the GluA2 Δ7 KI (hereafter, Δ7) genotype, which lacks the last 7 amino acids of the C-terminal tail of GluA2. The region lacking the 7 amino acids is essential for the interaction of GluA2 with PICK1 and GRIP1/2 on the synaptic membrane (15)(16)(17). Because of the mutations, these mice are believed to be devoid of LTD; however, we found in this study that LTD is still inducible under certain stimulation conditions.…”
mentioning
confidence: 52%
“…3A) (19,20). The patch pipette was filled with a Cs + -based internal solution to improve space clamping along PC dendrites by blocking K + channels (15,21). The mean Rm (membrane resistance in MΩ, measured by passing square currents through the patch pipette) in cells recorded with the pipette containing the Cs + -based internal solution was three-to four-times larger than those recorded with a pipette containing a K + -based solution (Table S1).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations